On a relation between memory effects by Maxwell - Boltzmann and Kelvin - Voigt in linear viscoelastic theory - Matarazzo, G. (Нелінійні коливання, 1999)
We study the smoothness properties of relaxation function such that a linear viscoelastic material system by Maxwell Boltzmann can be considered of Kelvin Voigt type; assuming that the relaxation function and its derivative decrease rapidly, and that the infinitesimal strain history is an analytical function, the Cauchy stress tensor of the linear viscoelasticity is well approximated by a constitutive functional of rate type. Вивчаються властивостi гладкостi релаксацiйної функцiї для випадку, коли лiнiйно пружна за Максвеллом Больцманом матерiальна система може розглядатись як система типу Кельвiна Войгта. У припущеннi, що релаксацiйна функцiя та її похiдна швидко спадають, а iнфiнiтезiмальна функцiя деформацiї є аналiтичною, показано, що тензор напруження Кошi в лiнiйнiй теорiї пружностi добре апроксимується складовим (конститутивним) функцiоналом коефiцiєнтного типу.